2013
DOI: 10.1186/1743-8977-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel lanthanide-labeled metal oxide nanoparticles improve the measurement of in vivo clearance and translocation

Abstract: The deposition, clearance and translocation of europium-doped gadolinium oxide nanoparticles in a mouse lung were investigated experimentally. Nanoparticles were synthesized by spray flame pyrolysis. The particle size, crystallinity and surface properties were characterized. Following instillation, the concentrations of particles in organs were determined with inductively coupled plasma mass spectrometry. The protein corona coating the nanoparticles was found to be similar to the coating on more environmentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 35 publications
5
95
1
Order By: Relevance
“…Three concentrations of AgSCs (0.1, 1.0, and 5.0 µg/mL) were chosen and added to the cells, followed by a 72-h incubation to determine changes in morphology, toxicity, and the expression of specific markers (i.e., MAP2, glial fibrillary acidic protein [GFAP], synaptophysin [Syn], postsynaptic density protein 95 [PSD-95], phosphorylated glycogen synthase kinase-3 [pGSK-3], and caspase-3). Recent studies conducted on rats have shown that these silver concentrations are relevant concentrations that might be found in rat brain tissue after in vivo exposure to AgNPs (Espinosa-Cristobal et al, 2013, Lee et al, 2013, Dziendzikowska et al, 2012). The dosimetry of nanomaterials, expressed as nanomaterial mass per volume and number of particles per volume, is summarized in Table 1.…”
Section: Methodsmentioning
confidence: 97%
“…Three concentrations of AgSCs (0.1, 1.0, and 5.0 µg/mL) were chosen and added to the cells, followed by a 72-h incubation to determine changes in morphology, toxicity, and the expression of specific markers (i.e., MAP2, glial fibrillary acidic protein [GFAP], synaptophysin [Syn], postsynaptic density protein 95 [PSD-95], phosphorylated glycogen synthase kinase-3 [pGSK-3], and caspase-3). Recent studies conducted on rats have shown that these silver concentrations are relevant concentrations that might be found in rat brain tissue after in vivo exposure to AgNPs (Espinosa-Cristobal et al, 2013, Lee et al, 2013, Dziendzikowska et al, 2012). The dosimetry of nanomaterials, expressed as nanomaterial mass per volume and number of particles per volume, is summarized in Table 1.…”
Section: Methodsmentioning
confidence: 97%
“…Samples were cooled to room temperature, an equal volume of 30% H 2 O 2 was added. Samples were reheated to 70°C for 2-4 h to break down remaining lipids and finally cooled to room temperature and diluted 10:1 with 3% HNO 3 for analysis by the UC Davis/Interdisciplinary Center for Plasma Mass Spectrometry using an Agilent 7500CE ICP-MS (Agilent Technologies, Palo Alto, CA) (Abid, 2013). The samples were introduced using a MicroMist Nebulizer (Glass Expansion, Pocasset, MA) into a temperature controlled spray chamber with Helium as the collision cell gas.…”
Section: Methodsmentioning
confidence: 99%
“…The organs were harvested 24 h after a single treatment, and showed that whilst the majority of NMs were retained within the lungs, some translocation of the NMs to the liver (15.9  0.9 ng-0.2% of total dose), kidneys (2.5  0.4 ng- 0.1 of total dose), heart (3.5  0.9 ng- 0.1% of total dose), spleen (2.6  0.1 ng- 0.1% of total dose), GT (69  35 ng-1.1% of total dose) and faeces (1306  301 ng-20.4% of total dose) occurred. The highest level of translocated NMs was found in the liver, with significant quantities found in the faeces, suggesting at a fast NM clearance from the lung into the GT (Abid et al 2013).…”
Section: Pharyngeal Aspirationmentioning
confidence: 96%